Auditorias ambientais de conformidade legal - Couto, Marcello Guimarães (2004)
There are different kinds of Environmental Audit, The Environmental Management System Audits are the most notorious one and the most known around the world one, due to the success of the organizatin's adoption of the ISO 14001 standard. Another kind of Environmental Audit that is wide accomplished is the Compliance Audit, that verifies if the applicable Environmental Legislation is beeing respected. In Brazil there is extensive federal, state and municipal legislation that make the cited Audit obligatory, in many times it is an integrant part of the Pollutioner Activity Permission System. These compulsory audits are an important instrument of the environmental management, producing important information to the management decisions. Although many legal documents demand it, there is a lack of regulamentation in most cases. In other cases, although it is regulamented, it is noticed that it doesen't achieve it's objectives, due to the inadequate qualification of the auditors, or due to a lack of qualified servants of the environmental agencies to analyse their written reports. In this dissertation we will try to approach the interfaces between both kinds of audit cited, as well as the utility of the compliance audit for the Environmental Management System. Special focus will be given to the research of the causes of the failure in achieving the legal objectives of the environmental compliance audits. The lack of structure and resources (including human resources) of the Environmental Agencies to demand the accomplishment and evaluate the results of the Compliance Audits, the lack of unequivocal criterion for the graduation of the auditor, as well as the lack of unequivocal criterion for the composition of the audit team, the lack of adequately qualified professionals at the market are the most important annoyance to the success of the cited audits